2005
DOI: 10.1103/physrevb.72.180502
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Meissner state and neither type-I nor type-II superconductivity in multicomponent superconductors

Abstract: Traditionally, superconductors are categorized as type-I or type-II. Type-I superconductors support only Meissner and normal states, while type-II superconductors form magnetic vortices in sufficiently strong applied magnetic fields. Recently there has been much interest in superconducting systems with several species of condensates, in fields ranging from Condensed Matter to High Energy Physics. Here we show that the type-I/type-II classification is insufficient for such multicomponent superconductors. We obt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
312
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(330 citation statements)
references
References 22 publications
16
312
1
1
Order By: Relevance
“…Also, for anisotropic superconductors, the theoretical calculation and analysis based on London theory and LowrenceDoniach theory has been shown that multiquanta vortex lattices will occur through changing titling angles of magnetic fields (equivalent to changing the value of q in this simulation) [25]. This suggests that our model is useful to study the vortex states for both low-κ type II superconductors and anisotropic superconductors, in addition to multiband or multicomponent superconductors [12].…”
Section: Vortex States and Vortex Chain Formation At Zero Temperaturementioning
confidence: 74%
See 2 more Smart Citations
“…Also, for anisotropic superconductors, the theoretical calculation and analysis based on London theory and LowrenceDoniach theory has been shown that multiquanta vortex lattices will occur through changing titling angles of magnetic fields (equivalent to changing the value of q in this simulation) [25]. This suggests that our model is useful to study the vortex states for both low-κ type II superconductors and anisotropic superconductors, in addition to multiband or multicomponent superconductors [12].…”
Section: Vortex States and Vortex Chain Formation At Zero Temperaturementioning
confidence: 74%
“…Although large amount of experimental and theoretical efforts in this field has been made [10][11][12][13][14][15][16][17][18], the nature of the vortex clustering in multiband superconductors is still an intensely controversial issue now [17,[19][20][21][22]. In principle, the vortex cluster formation means that there might exist some type of attraction between vortices in addition to repulsion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that a non-monotonous interaction potential between vortices (albeit without oscillating character) has recently been found in multicomponent superconductors by Babaev and Speight. [51] The authors have also predicted the existence of exotic (non-triangular) vortex-lattice structures.…”
Section: Effective Vortex Interaction Potential In Real Spacementioning
confidence: 98%
“…heavy fermion superconductors [16][17][18] and Sr2RuO4 [19,20]. Also, recently, two components GL equations are studied for two-band or two-gap superconductors, such as MgB2 [21,22]. …”
Section: Model: Two Components Ginzburg-landau Free Energymentioning
confidence: 99%